The Effects of Resistance Endurance Training on Muscle Architecture and Stem/Progenitor Cell Populations in a Murine Model of Rhabdomyosarcoma - Sanders, Olivia (Université d'Ottawa / University of Ottawa, 2022)
Background: Rhabdomyosarcoma (RMS) is a soft tissue malignancy of the skeletal muscle that occurs primarily in pediatric populations. The prevailing treatment for RMS is a combination of chemoradiation therapy and surgery which has contributed to its 5-year survival rate of 75%. However, the combination of RMS and chemoradiation therapy can lead to impaired muscle growth and development which results in life-long skeletal muscle atrophy and weakness for RMS survivors. Skeletal muscle is a highly plastic tissue due, in part, to dynamic interactions between muscle-resident stem and progenitor cells (i.e., satellite cells (SCs) and fibro/adipogenic progenitors (FAPs)), which are necessary for muscle maintenance, growth, and adaptation to anabolic stimuli such as resistance exercise training. There is a clear gap in research investigating whether resistance endurance training (RET) stimulates muscle growth and preserves muscle function after juvenile chemoradiation therapy. Purpose: To determine the extent to which RET ameliorates the skeletal muscle defects in a preclinical model of RMS survivorship. Hypothesis: RET will improve physical performance, muscle cross-sectional area (CSA), and stem/progenitor cell populations compared to sedentary mice following RMS and chemoradiation therapy. Methods: RMS (M3-9-M cells) was injected into a single hindlimb of juvenile (4 week) C57Bl/6 mice that underwent systemic chemotherapy followed by targeted, fractionated radiation therapy to the RMS-injected limb. Following therapy, mice underwent RET (RET; n=10) or remained sedentary (SED; n=10) for 8 weeks. Body composition and performance tests were completed pre- and post-therapy and throughout the exercise intervention. Fibre typing, cross-sectional area, myonuclear characteristics and trichrome staining were evaluated following muscle harvest and progenitor cell populations were assessed using flow cytometry. Results: RET led to increased endurance performance (p<0.0001) as well as a reduction in body fat percentage (p=0.0004). RET rescued atrophy induced by RMS+therapy as evidenced by a significant increase in gastrocnemius/soleus to body weight ratio for the RET group compared to the SED group (p=0.0303), despite the decrease in muscle weight observed in the treated limb compared to the control limb (p=0.015). A distinct increase in intramuscular fibrosis was noted in the treated limb compared to the control limb in both groups (p=0.0283). Furthermore, RET resulted in larger myofibre cross-sectional area (p<0.05) and a shift from Type IIX to IIA fibres (p<0.05). We also noted a greater Type IIA myonuclear domain in the RET group compared to the SED group (p=0.0015) and an overall decrease in myonuclear domain (the cytoplasmic volume controlled by each myonucleus) for the treated limb compared to the control limb (p<0.05). Interestingly, we noticed overall cell death and an increase in immune cells in the RMS treated limb, while exercise resulted in increased endothelial and mesenchymal stromal cells. Significance: These preclinical findings will provide the rationale for further investigation of the mechanisms responsible for the beneficial effects of RET as well as optimizing the RET protocol in this juvenile cancer survivorship model.
Keywords: fibrosis; cancer; radiation; chemotherapy; muscle satellite cells; fibro-adipogenic progenitors; exercise; inflammation